2021
DOI: 10.1101/2021.07.19.452943
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic insights into the differentiated population admixture structure and demographic history of North East Asians

Abstract: North China and South Siberia, mainly populated by Altaic-speaking populations, possess extensive ethnolinguistic diversity and serve as the crossroad for the initial peopling of America and western-eastern trans-continental communication. Yet, the complex scenarios of genetic origin, population structure, and admixture history of North-East Asia remain to be fully characterized, especially for Mongolic people in China with a genome-wide perspective. Thus, we genotyped genome-wide SNPs for 510 individuals from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…Genetic studies based on higher-resolution, genome-wide autosomal and uniparental Y-chromosome and mitochondrial deoxyribonucleic acid SNP data from 599 Northwest Han (Gansu Province) individuals showed increased genetic homogeneity in northwest Han individuals relative to the Mongolian/Turkic/Tungus and Tibetan–Burmese populations in the north ( Yao et al, 2021 ). The 986 previous genome-wide analyses from southernmost, central, and northern modern Han Chinese are consistent with the primary ancestry of modern southeastern coastal Han Chinese originating from northern China ( He G. et al, 2021 ; He G. G. et al, 2021 ). There was a genetic substructure in Shaanxi Han in terms of north–south-related ancestry corresponding well to latitudes ( He G. L. et al, 2021 ) and great genetic differentiation compared to Guizhou Han ( Wang et al, 2021 ).…”
Section: Discussionsupporting
confidence: 72%
“…Genetic studies based on higher-resolution, genome-wide autosomal and uniparental Y-chromosome and mitochondrial deoxyribonucleic acid SNP data from 599 Northwest Han (Gansu Province) individuals showed increased genetic homogeneity in northwest Han individuals relative to the Mongolian/Turkic/Tungus and Tibetan–Burmese populations in the north ( Yao et al, 2021 ). The 986 previous genome-wide analyses from southernmost, central, and northern modern Han Chinese are consistent with the primary ancestry of modern southeastern coastal Han Chinese originating from northern China ( He G. et al, 2021 ; He G. G. et al, 2021 ). There was a genetic substructure in Shaanxi Han in terms of north–south-related ancestry corresponding well to latitudes ( He G. L. et al, 2021 ) and great genetic differentiation compared to Guizhou Han ( Wang et al, 2021 ).…”
Section: Discussionsupporting
confidence: 72%
“…Besides, recent genomewide studies among Altaic-speaking populations in Northeast Asia have also found differentiated genetic admixture profiles between northern and southern Altaic-speaking populations and eastern and western Mongolians (He et al, 2021b). The reconstructed demographic models using ancient genomes further showed the Tungusic people keep a strong genetic homogeneity within populations, and the type of Tungusicdominant ancestry probably originated in a vast region from Mongolian Plateau to Amur River Basin about at least 16,000 years ago (He et al, 2021b;Mao et al, 2021). However, there are few genome-wide SNP data from Tungusic-speaking Manchu people reported so far.…”
Section: Introductionmentioning
confidence: 98%
“…Most genetic investigations based on the high-density genome-wide genetic variations from non-Altaic people in East Asia have revealed a fine-scale genetic landscape of genetic diversity and population admixture among the populations from different-language families (He et al, 2021a,c;Liu et al, 2021a,b;Wang et al, 2021d;Yao et al, 2021). Besides, recent genomewide studies among Altaic-speaking populations in Northeast Asia have also found differentiated genetic admixture profiles between northern and southern Altaic-speaking populations and eastern and western Mongolians (He et al, 2021b). The reconstructed demographic models using ancient genomes further showed the Tungusic people keep a strong genetic homogeneity within populations, and the type of Tungusicdominant ancestry probably originated in a vast region from Mongolian Plateau to Amur River Basin about at least 16,000 years ago (He et al, 2021b;Mao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic evidence inferred from the STR, SNP, InDel in the autosomal, X/Y-chromosomes has demonstrated that China with massive ethnolinguistic diversity harbored multiple genetic diversity [24][25][26][27][28]. Recent genetic analyses based on the genome-wide SNP data have revealed the obvious fine-scale population stratifications among the populations from different language families, such as significant genetic differences were identified between Sinitic-speaking Han Chinese and Tungusic/Mongolic/Turkic people in the north [29], Tibeto-Burman people in the southwest [30], and Tai-Kadai, Hmong-Mien, Austronesian and Austroasiatic speakers in the south [31]. Although these aforementioned genetic substructures of Chinese populations have been characterized through SNPs [32], the atlas of the genetic structures of Chinese populations are not fully understood and need further investigation to shed light the fine-scale structures for forensic purposes.…”
Section: Introductionmentioning
confidence: 99%